Knowledge and leadership of the sub-districts health promoting hospital director in preventing the spread of Coronavirus 2019 based on COVID-Free setting, Lopburi Province - Maneechay, Mano; Saisum, Bunnaris; Maneechay, Surin (Journal of Medical and Public Health Region 4, 2026)
This research is a descriptive study aimed to examine the knowledge and leadership qualities in the management of organizations to prevent the spread of the 2019 Coronavirus (COVID-19), according to the COVID Free Setting measures for organizations. The study focused on directors of sub-district health-promoting hospitals under the Lopburi Provincial Public Health Office. A questionnaire was used as the research tool. The population studied included 123 directors or acting directors of sub-district health-promoting hospitals in Lopburi Province. Data were analyzed using descriptive statistics, including frequency, percentage, mean, and Pearson’s correlation coefficient. The results revealed that the sample group had a high overall level of knowledge about COVID-19, very high overall leadership qualities, and a good overall level of compliance with the COVID Free Setting measures for organizations (μ = 2.89, σ = 0.18). The recommendation is to promote the implementation of COVID Free Setting measures in all units to serve as a guideline for monitoring and preventing the spread of COVID-19 and other respiratory infectious diseases in the future.